SELECTING RESPONDENTS FOR SURVEY QUESTIONNAIRE IN ISLAMIC WAY - Asadullah Shah; Zubair Ahsan; Fahad Shah Bukhari; Mohamed Abbas; Faisal Shah (Journal of Islamic, Social, Economics and Development, 2017)
The main objective of this study is to identify key attributes of a respondent to deem him worthy and reliable for the purposes of a survey questionnaire. These key attributes are based on the teachings of the Qur’an. As the Holy Qur’an is the word of Almighty Allah and it contains absolute knowledge. In this paper, various human traits are identified and described in the light of Quran to determine whether a person can be a respondent in a survey questionnaire study or not. This paper also highlights the types of questions in survey questionnaires and distinguishes which type of questions are used for qualitative and/or quantitative research. Additionally, this paper emphasizes on the problems with data collection and samplings, as well as stresses on the problems of probabilistic and non-probabilistic sampling